Peradaban Islam Rasulullah Periode Mekkah (622-632): Fondasi Awal dalam Sejarah Perkembangan Islam - Raskita Mega Wati Br.Pinem; Siti Aisyah; Fiza Ikramullah Lubis; Siti Nur Ainun; Shirajul Fuadi (Reflection : Islamic Education Journal, 2025)
This study examines the development of Islamic civilization during the time of the Prophet Muhammad (peace be upon him) using an approach that rejects the conceptual dichotomy between the Meccan and Medina phases. The title "Meccan Period (622–632 CE)" in this context is not interpreted geographically, but rather as a historical and substantial continuation of Islamic values instilled in Mecca before 622 CE and culminating in the socio-political institutions in Medina after the Hijrah. This study uses a qualitative method with a literature study approach to examine the causal relationship between the spiritual foundations instilled in Mecca and the development of Islamic civilization institutions in Medina. The results of the study indicate that the Meccan period was a phase in the formation of the spiritual and moral character of Muslims through the strengthening of the values of monotheism, patience, justice, and noble character amidst social and political pressures. These values formed a solid ideological basis for the formation of a civilized Islamic society. After the Hijrah to Medina, these values were not only maintained but also systematically institutionalized. This is reflected in several important aspects, such as the drafting of the Medina Charter as the basis of the constitution that guarantees plurality and social justice, the establishment of the Prophet's Mosque as a center of religious and governmental activities, the regulation of the economic system through the prohibition of usury and the obligation of zakat as a form of equitable distribution of wealth, and the development of an educational system that emphasizes the integration of knowledge and manners. Thus, it is concluded that the consolidated Islamic civilization until 632 AD was the result of a development process based on spiritual and moral values that had been intensively instilled since the early phase in Mecca. This study emphasizes the importance of value continuity in the process of social transformation, as well as the relevance of a spiritual approach in the development of an inclusive, just, and sustainable civilization.